Microbial abundance and diversity patterns associated with sediments and carbonates from the methane seep environments of Hydrate Ridge, OR - Marlow, Jeffrey J.; Steele, Joshua A.; Case, David H.; Connon, Stephanie A.; Levin, Lisa A.; Orphan, Victoria J. (Frontiers in Marine Science, 2014)
Methane seeps are among the most productive habitats along continental margins, as anaerobic methane-oxidizing euryarchaeaota and sulfur-metabolizing deltaproteobacteria form the biological base of a dynamic deep-sea ecosystem. The degree of methane seepage therefore represents one important variable in ecosystem dynamics, and the recent discovery of carbonate-hosted endolithic methanotrophy exposes another potentially discriminating factor: physical substrate type. Methanotrophic microbial communities have been detected within diverse seep-associated habitats, including unlithified sediments, protolithic carbonate nodules, and lithified carbonate slabs and chemoherms of distinct mineralogies. However, a systematic assessment of the diversity and community structure associated with these different habitats has been lacking. In this study, microbial aggregate analysis, microbial abundance quantification, mineralogical identification, and archaeal and bacterial 16S rRNA gene clone libraries were used to deconvolve the relationships between seepage activity, substrate type, and microbial community structure. We report prevalent methane-oxidizing archaeal lineages in both active and low-activity seep settings, and a strong community dependence on both seepage activity and substrate type. Statistical treatments of relative taxa abundances indicate that archaeal community structure is more dependent on the degree of methane seepage than physical substrate type; bacterial assemblages appear to be more strongly influenced by the type of colonization substrate than seepage activity. These findings provide a window into the determinants of community structure and function, improving our understanding of potential elemental cycling at seep sites.